Characterization of Disrupted Tissue Interface Thickness for Keratorefractive Lenticule Extraction Procedure With ELITA Femtosecond Laser - Minoguchi, Hajime; Umar, Athiyya; Fu, Hong (Translational vision science & technology, 2024)
This study identified and compared variables causing changes in corneal tissue structure following the smooth incision lenticular keratomileusis (SILK) procedure using the ELITA Femtosecond Laser System by characterizing the resulting disrupted tissue interface. Seventy-one ex vivo porcine eyes and six human cadaver eyes underwent ELITA SILK with diverse surgical steps, pulse energies, scan overlaps, and surgical methods. Flaps created with the iFS Advanced Femtosecond Laser and ELITA systems were also evaluated. The disrupted interface thickness was determined by imaging corneal layers at different depths through the interface with confocal microscopy and counting layers with elevated backscattered light via computer program-assisted, subject-matter-expert visual judgment with blinding. The disrupted interface thickness for ELITA SILK was 25 ± 3 µm; for the ELITA flap, it was 25 ± 2 µm; and for the iFS flap, it was 32 ± 3 µm. Factors influencing the total ELITA SILK disrupted interface thickness included laser pulse energy (0.11 µm/nJ; P < 0.01), scan overlap (5 µm; P < 0.01), and mechanical manipulation (7 µm; P < 0.01). Varying surgical techniques for mechanical manipulation resulted in a difference in disrupted interface thickness of 4 µm (P < 0.01). The ELITA SILK disrupted interface thickness was less than that of the iFS flap and similar to that of the ELITA flap. Assessing disrupted interface thickness identified factors influencing the quality of the corneal interface with SILK. The disrupted interface thickness, a new method for measuring corneal damage, has been used to quantify the potential effects of various refractive surgery factors on surgical outcomes.